Effects of Supplementation of Alkaloid and Non Alkaloid from Sauropus androgynus Leaves on Egg Production and Lipid Profil in Layer Chicken - Santoso, U; Suteky, T; Fenita, Y (ANIMAL PRODUCTION, 2010)
The present study was conducted to evaluate effects of supplementation of alkaloid or non alkaloid from Sauropus androgynus leaves on productive performance and the contents of lipid fractions in layer chickens. Forty two layer chickens aged 30 weeks were distributed to seven treatment groups. Each treatment group contained six layer chickens maintained in an individual cage, respectively. The present experiment used completely randomized experimental design. The seven treatment groups were as follows: 1)  Control, layer chickens were fed diet without supplementation of alkaloid or non alkaloid extracted from Sauropus androgynus (P0);  2)  Layer chickens were fed diet contained 30 mg non alkaloid/kg diet (P1); 3)  Layer chickens were fed diet contained 60 mg non alkaloid/kg diet (P2); 4)  Layer chickens were fed diet contained 90 mg non alkaloid/kg diet (P3);  5)  Layer chickens were fed diet contained 30 mg  alkaloid/kg diet (P4);  6)  Layer chickens were fed diet contained 60 mg alkaloid/kg diet (P5); 7) Layer chickens were fed diet contained 90 mg alkaloid/kg diet (P6). Layer chickens were fed experimental diet with 2,750 kcal/kg Metabolizable Energy (ME) and 16.0% protein. Diet and drinking water were fed ad libitum. Experimental results showed that supplementation of alkaloid or non alkaloid from Sauropus androgynus leaves significantly affected productive performance in layer chickens. It appear that non alkaloid supplementation had no advantage in improving productive performance, whereas supplementation of 30 mg alkaloid/kg diet might have advantages in improving productive performance as indicated by better egg production and lower feed conversion ratio. Treatment had no effect on glucose and triglyceride concentration in serum, but it affected total cholesterol, HDL-cholesterol, LDL+VLDL-cholesterol and atherogenic index in serum. Cholesterol concentration in serum was significantly increased in P4 and P6, whereas HDL-cholesterol concentration was significantly increased in P1, P2, P3, P4 and P5 as compared with the control group. Atherogenic index was significantly lower in P1, P2, P3, P4 and P5 as compared with control group. Egg yolk content was significantly lower in P5 as compared with the control group. Fatty liver score was significantly lower in P1, P2, P4, P5 and P6 as compared with the control group. Abdominal fat was significantly lower in P1, P4 and P6 as compared with the control group. Staphylococcus sp. in eggshell was significantly reduced in layer chickens fed diet with 30 mg non alkaloid/kg diet or 90 mg alkaloid/kg diet, whereas Escherichia coli was not reduced by the treatments.  In conclusion, both alkaloid and non alkaloid from Sauropus androgynus leaves were effective to reduce the risk of atherosclerosis occurrence. In addition, alkaloid was more effective in lowering egg cholesterol than non alkaloid. Both alkaloid and non alkaloid at a given level of supplementation reduced Staphylococcus sp. in eggshell. (Animal Production 12(3): 184-189 (2010)Key Words: alkaloid, non alkaloid, Sauropus androgynus, atherogenix index, cholesterol